2012
DOI: 10.1210/er.2011-0013
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Mast Cells and Macrophages in Cardiovascular and Metabolic Diseases

Abstract: Mast cells are essential in allergic immune responses. Recent discoveries have revealed their direct participation in cardiovascular diseases and metabolic disorders. Although more sophisticated mechanisms are still unknown, data from animal studies suggest that mast cells act similarly to macrophages and other inflammatory cells and contribute to human diseases through cell-cell interactions and the release of proinflammatory cytokines, chemokines, and proteases to induce inflammatory cell recruitment, cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 395 publications
0
59
0
Order By: Relevance
“…The mean and standard deviation (mean ± SD) of continuous and normal distributional variables and median and interquartile range of conof MCs in diet-induced obesity and diabetes, MCs inhibitory medications used in obesity and diabetes in experimental models offer hope to patients with these common chronic inflammatory diseases [19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean and standard deviation (mean ± SD) of continuous and normal distributional variables and median and interquartile range of conof MCs in diet-induced obesity and diabetes, MCs inhibitory medications used in obesity and diabetes in experimental models offer hope to patients with these common chronic inflammatory diseases [19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that MCs participate in the pathogenesis of inflammatory diseases such as cardiovascular diseases and metabolic disorders, MCs dysfunction has been viewed as the main offenders in some chronic inflammatory disorders, but the exact mechanisms of MCs in the pathogenesis of these diseases are not fully understood [19][20][21][22][23][24][25][26][27][28]. Participating of MCs in inflammatory diseases can be activated by non-allergic triggers, such as cytokines, often having synergistic effects among them [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various immune [5]. In the immune cells, macrophage infiltration and polarisation primarily contribute to adipose tissue inflammation and insulin resistance [7,8]. Furthermore, other immune cells can affect adipose tissue inflammation by regulating macrophage polarisation [5,34].…”
Section: Discussionmentioning
confidence: 99%
“…Of all the immune cells, adipose tissue macrophages (ATMs) have been paid a great deal of attention and are regarded as critical to the development of obesity-associated inflammation and insulin resistance [7,8]. Epididymal adipose tissue (EAT) has been reported to be the most commonly used visceral fat depot in mouse studies, and its macrophage infiltration is most severe during the development of DIO [9].…”
Section: Introductionmentioning
confidence: 99%